2020
DOI: 10.7150/jca.40767
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of an Individualized Nomogram for Predicting Survival in Patients with Esophageal Carcinoma after Resection

Abstract: An accurate estimation of prognosis of the esophageal carcinoma patients after surgery is urgently needed. Clinical nomogram has been developed to quantify risk by incorporating prognostic factors for individual patient. Based on the Surveillance, Epidemiology, and End Results (SEER) database from 2004 to 2013, a total of 4566 patients were selected. Of those, 3198 patients were assigned to training set to construct the nomogram, which incorporated age, gender, histology, grade, T stage, N stage, nodes examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
28
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 17 publications
1
28
1
Order By: Relevance
“…*P < 0.05, **P < 0.01, ***P < 0.001. system has high specificity, stability, accuracy, and sensitivity, which makes it convenient for clinical practice (37). The use of the TNM staging, the most commonly used indicator in prognosis and treatment, is still controversial because it is based on the limited anatomical range of tumors without the consideration of any other prognostic biomarkers (38). Therefore, our study integrated TNM staging and PEDF expression to estimate the OS of ESCC patients, and the 1-, 3-, and 5-year AUC values of the nomogram indicated that it was more accurate for predicting prognosis than the TNM stage ( Figure 3C).…”
Section: Discussionmentioning
confidence: 99%
“…*P < 0.05, **P < 0.01, ***P < 0.001. system has high specificity, stability, accuracy, and sensitivity, which makes it convenient for clinical practice (37). The use of the TNM staging, the most commonly used indicator in prognosis and treatment, is still controversial because it is based on the limited anatomical range of tumors without the consideration of any other prognostic biomarkers (38). Therefore, our study integrated TNM staging and PEDF expression to estimate the OS of ESCC patients, and the 1-, 3-, and 5-year AUC values of the nomogram indicated that it was more accurate for predicting prognosis than the TNM stage ( Figure 3C).…”
Section: Discussionmentioning
confidence: 99%
“…So far, the tumor node metastasis (TNM) classi cation is the most commonly utilized tool for predicting the prognosis in cancer patients [29]. However, increasing evidences demonstrated the unsatisfactory discriminative capacity of TNM system in predicting clinical outcomes [30,31]. With the development of life science and technology, more and more prognostic markers have been identi ed for ESCA [3].…”
Section: Discussionmentioning
confidence: 99%
“…computed tomography (CT) was used to rule out distant metastasis and determine the initial stage. Carcinoma in situ can be treated by endoscopic mucosal resection, while local tumors with or without regional lymph node metastasis can be treated by esophagectomy, chemotherapy, chemotherapy or combination therapy [8,9]. Unresectable tumors or tumors with distant metastases outside the region are treated with palliative interventional therapy [10].…”
Section: Introductionmentioning
confidence: 99%